Palliative care: needs of advanced breast cancer patients - Cherny NI (Dove Medical Press, 2018)
Nathan I Cherny, Shani Paluch-Shimon, Yael Berner-Wygoda Integrated Oncology and Palliative Medicine Department, Breast Oncology Unit, Shaare Zedek Medical Center, Jerusalem, Israel Abstract: Advanced breast cancer is characterized by many physical manifestations with the potential to undermine the quality of life (most related to the cancer and some to treatments), as well as substantial impact on psychosocial well-being. Patients with advanced breast cancer and their families have complex needs that have to be addressed in order to minimize severe distress and deterioration in the quality of life of patients and their family members. This task requires the full engagement of an interdisciplinary approach to palliative care with strong emphasis on the assessment of needs and anticipated needs, patient expectations, skilled therapeutics, and commitment to continuity of care. In this review, we address four issues: 1) organizational and conceptual issues in palliative care of patients with breast cancer, 2) common physical symptoms among patients with breast cancer and their management, 3) common psychological issues among patients with breast cancer, and 4) common challenging palliative care problems in breast cancer. Keywords: psychooncology, supportive care, goal setting, quality of life